A phase I trial of the mTOR inhibitor temsirolimus in combination with capecitabine in patients with advanced malignancies. (27th February 2021) - Trivedi, Neel D.; Armstrong, Samantha; Wang, Hongkun; Hartley, Marion; Deeken, John; Ruth He, A.; Subramaniam, Deepa; Melville, Heather; Albanese, Chris; Marshall, John L.; Hwang, Jimmy; Pishvaian, Michael J.
ABSTRACT: Background: Temsirolimus is an mTOR antagonist with proven anticancer efficacy. Preclinical data suggest greater anticancer effect when mTOR inhibitors are combined with cytotoxic chemotherapy. We performed a Phase I assessment of the combination of temsirolimus and capecitabine in patients with advanced solid tumors. Methods: Patients were enrolled in an alternating dose escalation of temsirolimus (at 15 or 25 mg IV weekly) and capecitabine (at 750, 1000, and 1250 mg/m 2 twice daily) in separate Q2‐week and Q3‐week cohorts. At the recommended Phase II doses (RP2Ds) of temsirolimus and capecitabine (Q2), seven patients were also treated with oxaliplatin (85 mg/m 2, day 1) to determine triplet combination safety and efficacy. Results: Forty‐five patients were enrolled and 41 were evaluable for dose‐limiting toxicities (DLTs). The most common adverse events (AEs) were mucositis, fatigue, and thrombocytopenia. The most common grade 3/4 AEs were hypophosphatemia and anemia. Five patients had DLTs, including hypophosphatemia, mucositis, and thrombocytopenia. The RP2Ds were temsirolimus 25 mg +capecitabine 1000 mg/m 2 (Q2); and temsirolimus 25 mg +capecitabine 750 mg/m 2  (Q3). Of the 38 patients evaluable for response, one had a partial response (PR) and 19 had stable disease (SD). The overall disease control rate was 52%. Five of the 20 patients with SD/PR maintained disease control for >6 months. Conclusions: The combination of temsirolimus and capecitabine is safe on both a Q2‐week and a Q3‐week schedule. The combination demonstrated promising evidence of disease control in this highly refractory population and could be considered for testing in disease‐specific phase II trials. Abstract : This manuscript describes a Phase I clinical trial of the combination of temsirolimus and capecitabine in the treatment of patients with advanced solid tumors. We determined that this combination is safe on both a Q2‐week and a Q3‐week schedule. Together, temsirolimus and capecitabine also demonstrated promising evidence of disease control in this highly refractory population, and we believe the combination should be considered for testing in disease‐specific phase II trials.